Ovarian cancer? Wait for results - Azizan, Azha Syahril; Awang, Mokhtar; R.Z, Alik; Bilal, Hakim Gharib; Abdulwahab, Dalia F (Obstetrical & Gynaecological society of malaysia, 2010)
She was a 30 years old Para 2 with her last child birth 2 years ago, she had a regular menstrual period and that she was not on any contraceptive method. With a month's history of abdominal distension and a cystic mass of 24 weeks equivalent of gravid uterus, no sign and symptoms of urinary, bowel, cardiac or respirotory problems. With CA 125 of 406, and suggestivesonographic features. The diagnosis of bilateral ovarian tumour with possible liver metastasis could easily be entertained. However total abdominal hysterectomy with bilateral salpingo-oopherectomy specimen showed casseating epithiloid granulomatous inflamation in both tubo-ovarian masses, compatible with tuberculosis. The same features were found on left lymph node peritoneum. AND THESE WERE THE RESULTS